Matrix metalloproteinases and their tissue inhibitors direct cell fate during cancer development - Hojilla, C V (Nature Publishing Group, 2003)
Matrix metalloproteinases (MMPs) were initially recognised for their extracellular matrix (ECM)-degrading capability during tissue remodelling. Their importance was further highlighted by their role in metastasis. Clinical trials have since evaluated the potential of MMP inhibitors as anticancer therapeutics, but without success. These initial studies point to the complex, multifunctional capacity of MMPs in cancer as shown by their function, not only as strident mediators of advanced malignancies, but also as effectors of early stage tumorigenesis. Research now shows that MMPs, and their tissue inhibitors, affect tumour initiation and growth through loss of cell adhesion, evasion of apoptosis, and deregulation of cell division. The extracellular nature of the metalloproteinase axis situates it as a master regulator of cell fate.